Analisis Pengaruh Institusi terhadap Strategi dan Kinerja Badan Usaha Milik Negara (BUMN) - Siswaji, Bambang; Nuryartono, Nunung; Arifin, Bustanul; Said Didu, Muhammad (Jurnal Manajemen Teknologi, 2013)
Based on literatures, institutions (rules of the game) influence strategy that leads to performance of enterprise. If the relationships hold for SOE, the improvement of institutional environment will enable the improvement of SOE's performance. The aim of this research is to prove the causal relationship of institution-strategy and strategy-performance in SOE environment, and to extend the relationship to institution-performance of SOE. Likert-scaled data have been collected from expert's opinion survey. Structural equation modeling analyses found: 1) institutions significantly influence strategy; 2) strategy does not influence performance significantly; and 3) institutions directly affect performance of SOE. The reserach has been completed with historical institutional analysis to elaborate how institutional factors have emerged and developed. It found a chain of historical events that have become critical junctures and shaped the institutional factors of SOE. The research showed that favorable institutional environment is importance as pre-condition to improve SOE's performance, and it needs time and consistent efforts to develop.Keywords: enterprise performance, historical institutional analysis, institution-based strategy, state-owned enterprise, structural equation modeling